Pelatihan Pengenalan Aplikasi Office Online dan Teknologi kepada Siswa/i Sekolah Dasar Di SD Negeri 47/IV Kota Jambi - Masgo; Mery; Laura Prasasti (Jurnal Pengabdian Masyarakat UNAMA, 2023)
Many elementary school (SD) students today still do not know computers let alone computer applications, even though today the role of computers is very important. For this reason, computer applications should be taught since elementary school so that they have expertise in the field of computers as a provision for continuing the junior high school level, because at the junior high school level informatics lessons have been included in the compulsory curriculum, especially schools that have adopted driving schools. For this reason, this community service activity participants are students of SD Negeri 47/IV Jambi City, especially class IV, where the school has not implemented online office applications, therefore, this service aims to provide computer science about basic office applications. The implementation method for this service activity is with the following steps : (1) Introduction to basic Office applications, namely Word and Power Point, (2) Practice how to edit with Word and make presentation slides, (3) Directions for using Office applications by providing brief exercises, (4) evaluation